Brain structure abnormalities in adolescent girls with conduct disorder. (22nd October 2012) - Fairchild, Graeme; Hagan, Cindy C.; Walsh, Nicholas D.; Passamonti, Luca; Calder, Andrew J.; Goodyer, Ian M.
<x xml:space="preserve">Abstract</x> Background: Conduct disorder (CD) in female adolescents is associated with a range of negative outcomes, including teenage pregnancy and antisocial personality disorder. Although recent studies have documented changes in brain structure and function in male adolescents with CD, there have been no neuroimaging studies of female adolescents with CD. Our primary objective was to investigate whether female adolescents with CD show changes in grey matter volume. Our secondary aim was to assess for sex differences in the relationship between CD and brain structure. Methods: Female adolescents with CD (n = 22) and healthy control participants matched in age, performance IQ and handedness (n = 20) underwent structural magnetic resonance imaging. Group comparisons of grey matter volume were performed using voxel‐based morphometry. We also tested for sex differences using archive data obtained from male CD and control participants. Results: Female adolescents with CD showed reduced bilateral anterior insula and right striatal grey matter volumes compared with healthy controls. Aggressive CD symptoms were negatively correlated with right dorsolateral prefrontal cortex volume, whereas callous‐unemotional traits were positively correlated with bilateral orbitofrontal cortex volume. The sex differences analyses revealed a main effect of diagnosis on right amygdala volume (reflecting reduced amygdala volume in the combined CD group relative to controls) and sex‐by‐diagnosis interactions in bilateral anterior insula. Conclusions: We observed structural abnormalities in brain regions involved in emotion processing, reward and empathy in female adolescents with CD, which broadly overlap with those reported in previous studies of CD in male adolescents.